The relationship of office ergonomic towards job performance among lower level management at Petronas Penapisan Melaka, Malaysia / Nurfarahin Amzah...[et al] - Amzah, Nurfarahin (Faculty of Business and Management, 2013)
The purpose of this study is to determine the relationship between ergonomic toward job performance at lower level management, PETRONAS Penapisan Melaka. An ergonomics has three elements which are Office Setting, Office Furniture, Office Equipment. The sample was randomly selected from lower level management at PETRONAS Penapisan Melaka using the probability sampling strategy. The simple random sampling (SRS) technique was choosen to select the sample size. The data were analyzed using SPSS version 18.00 to simultaneously measure the relationship of three independents variables toward job perfonnance in the organization. The questionnaire was distributed 150 set to the respondents and only 130 were returns back by the respondents. As a conclusion, the three independent variables of ergonomic had relationship toward job perfonnance of lower level management at PETRONAS Penapisan Melaka. The findings concluded that, there is significant relationship between ergonomic toward job perfomance.